Kajian Fikih Tentang Kepemimpinan Perempuan dan Gerakan Kesetaraan Gender di Indonesia - muh sagenang (Sekolah Tinggi Agama Islam Babussalam Sula, 2026)
The issue of women’s leadership in Islam remains a subject of ongoing debate, particularly within Indonesian Muslim society, which is confronted with social change and increasing demands for gender equality. This article aims to examine Islamic jurisprudential perspectives on women’s leadership and analyze their relevance to the principle of gender equality in the Indonesian context. This study employs a qualitative method using a library research approach by analyzing classical and contemporary fiqh sources, the Qur’an, hadith, and relevant academic literature. The findings indicate that classical Islamic jurisprudence tends to restrict women’s leadership in the public sphere, largely due to textual interpretations and patriarchal socio-historical contexts during the period of its formation. In contrast, contemporary Islamic jurisprudence, through contextual interpretation and the maqāṣid al-sharī‘ah framework, opens space for legitimizing women’s leadership by emphasizing the principles of justice, public benefit, and competence. In the Indonesian context, the practice of women’s leadership is consistent with constitutional values and does not contradict the fundamental principles of Islamic teachings, thereby necessitating a more adaptive and socially responsive jurisprudential approach.